A Novel ELF4 Gene Variant Disrupts T and NK Cell Function in a Patient with Immune Thrombocytopenia (ITP) - Kendirli, Perihan Kader; Gök, Veysel; Eken, Ahmet; Özcan, Alper; Erdem, Şerife; Kısaarslan, Ayşenur Paç; Kayhan, Eda (Springer Basel AG, 2026)
Objective and design In this report, we identified a novel hemizygous ELF4 variant (c.1822G > C; p.Gly608Arg) in an adolescent male with chronic immune thrombocytopenia (ITP) and performed functional immunologic characterization. Materials and methods Peripheral blood mononuclear cells (PBMCs) of the patient and age-matched controls were characterized by flow cytometry with respect to T cell phenotype, activation, proliferation and NK cell cytotoxicity. Results The p.Gly608Arg substitution affects a highly conserved residue in the C-terminal regulatory domain of ELF4 and is predicted to be damaging. Immunophenotyping showed an expanded CD8(+) T-cell compartment, an inverted CD4/CD8 ratio, reduced na & iuml;ve T-cell populations, and accelerated acquisition of memory-like phenotypes upon activation. Both CD4(+) and CD8(+) T cells displayed increased proliferation following TCR stimulation, consistent with impaired ELF4-dependent regulation of effector T-cell expansion. NK cells exhibited reduced granzyme B and perforin expression and markedly diminished cytotoxicity against K562 targets, indicating defects in maturation and effector function. Conclusions These findings suggest that the identified ELF4 variant is associated with combined T- and NK-cell dysfunction. This case expands the clinical spectrum of Deficiency in ELF4, X-linked and underscores the relevance of evaluating ELF4 mutations in patients with unexplained cytopenias accompanied by dysregulated lymphocyte activation and impaired cytotoxic responses.
Keywords: ELF4; X-linked; ITP; Deficiency in ELF4